The effect of artificial intelligence on the improvement of prosthetic hands - Kuts, Maksym; Bozhok, Natalia (My University, 2020)
У науковій роботі розглянута актуальна тема сьогодення - автоматичні протези рук. За даними Організації охорони здоров’я, по всьому світу є понад 40 мільйонів ампутацій. У тезах досліджено новітні досягнення технології протезування рук, які значно покращили якість життя ампутованих верхніх кінцівок. Визначено також прогалини, які залишаються в контролі протезування рук, зокрема, у використанні природних електричних сигналів з м'язів пацієнта. The following scientific paper considers a very relevant topic - automatic hand prostheses. There are more than 40 million amputees across the globe, according to the Health Organization. In this paper it was investigated the recent, innovative advances in prosthetic hands technology which greatly improved the quality of life for upper-limb amputees. However, it was also defined the gaps remaining in the control of prosthetic hands, specifically in using naturally generated electric signals from the patient's muscles.
Keywords: штучний інтелект; кафедра ділової іноземної мови та міжнародної комунікації; artificial intelligence; протези рук; prosthetic hands